DEVELOPMENT OF DIGITAL LEARNING RESOURCES USING SMART APPS CREATOR IN CLASS VIII SCIENCE SUBJECTS - Syahrul Mubaroq; Aulya Nanda Prafitasari (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
This article aims to develop Android-based digital learning resources using smart apps creators for science subjects for class VIII. The type of development model used in this development research is the Lee Owens model with the following stages; (1) analysis consisting of needs assessment and front end analysis (2) design, (3) development, (4) implementation, and (5) evaluation. The resulting product development shows that 25% consider it very easy to use, 47% easy, and 19.6% quite easy. While the percentage which shows that 51% of students are very enthusiastic in learning to use this product. Then as much as 23.5% assess the number of students' interest in using android applications for learning is at a sufficient level. Meanwhile, 17.6% of students' interest in using android applications for learning is at a sufficient level.This article aims to develop Android-based digital learning resources using smart apps creators for science subjects for class VIII. The type of development model used in this development research is the Lee Owens model with the following stages; (1) analysis consisting of needs assessment and front end analysis (2) design, (3) development, (4) implementation, and (5) evaluation. The resulting product development shows that 25% consider it very easy to use, 47% easy, and 19.6% quite easy.While the percentage which shows that 51% of students are very enthusiastic in learning to use this product. Then as much as 23.5% assess the number of students' interest in using android applications for learning is at a sufficient level. Meanwhile, 17.6% of students' interest in using android applications for learning is at a sufficient level.